Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.2252.7741
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Fidelity Adaptive Sampling Method for Metamodel-Based Uncertainty Quantification of Computer Simulations

Abstract: A multi-fidelity global metamodel is presented for uncertainty quantification of computationally expensive simulations. The multi-fidelity approximation is built as the sum of a low-fidelity-trained metamodel and the metamodel of the difference (error) between high-and low-fidelity simulations. The metamodel is based on dynamic stochastic radial basis functions, which provide the prediction along with the associated uncertainty. New training points are added where the prediction uncertainty is largest, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…1. Typically, a two step strategy is used in multi-fidelity adaptive sampling strategy [30], where in the first step x * is determined without considering the cost impact. Once x * is determined, then fidelity of analysis is decided based on the cost ratio between high and low fidelity analyses.…”
Section: Adaptive Sampling In Multi-fidelity Gpmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Typically, a two step strategy is used in multi-fidelity adaptive sampling strategy [30], where in the first step x * is determined without considering the cost impact. Once x * is determined, then fidelity of analysis is decided based on the cost ratio between high and low fidelity analyses.…”
Section: Adaptive Sampling In Multi-fidelity Gpmentioning
confidence: 99%
“…We found that the adaptive sampling schemes for the multi-fidelity GP surrogate are two step process, where in the first step location or design point on input parameters are determined by finding the location of maximum predictive uncertainty. Then in the second step, decision is made whether to run high-fidelity or low-fidelity analysis based on the cost ratio of these analyses [30]. In this work a new criteria is proposed where the selection of next design point as well as fidelity is done in a single step.…”
Section: Introductionmentioning
confidence: 99%